CIRCULAR ECONOMY IN FASHION INDUSTRY: BIBLIOMETRIC ANALYSIS OF 2017-2022 - Sawalkar, Rohini; Saxena, Vimal Deep; Gaikwad, Vishal B; Phule, Prashant N (The journal of contemporary issues in business and government, 2022)
Circular economy in recent time has gained a lot of significance. The concept has multidimensional benefits to stakeholders and positive impact on the environment. Fashion industry on the other is one of the fastest growing industries. The industry largely contributes to various pollutions though. The industry is consuming resources at a faster pace and need to be controlled at a point to achieve the UN Sustainable Development Goals. Implementation of circular economy in fashion industry will help to contribute for the attainment of multiple SDGs. The objective of this paper was to conduct bibliometric analysis using R studio application in the field of circular economy and fashion industry. Scopus data base was considered for the span of 2017-2022 to extract the literature on the aimed concepts. Total of 80 documents were analysed. Sustainability was the most productive source with total of 47 journals. The highly contributing country was UK, followed by Italy, Spain, Australia, and India. The study helps to initiate new approaches to strengthen adaption and application of circular economy.